2020
DOI: 10.1175/jpo-d-20-0029.1
|View full text |Cite
|
Sign up to set email alerts
|

The Regeneration of the Lofoten Vortex through Vertical Alignment

Abstract: Observations from the past decades have promoted the idea of a long-lived anticyclonic vortex residing in the Lofoten Basin. Despite repeatedly recorded intense anticyclones, the observations cannot firmly decide whether the signature is of a single vortex or a succession of ephemeral vortices. A vortex persisting for decades requires some reinvigoration mechanism. Wintertime convection and vortex merging have been proposed candidates. We examine Lofoten Basin vortex dynamics using a high-resolution regional o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 179 publications
4
32
0
Order By: Relevance
“…The exchange of AW with the LB (AW-LB exchange) has also been studied extensively. Earlier literature has suggested that much of the warm AW in the LB stems from anticyclonic eddies in the form of long-lived coherent vortices that shed off from the Slope Current and then bring with them heat and vorticity westward into the basin (Köhl, 2007;Isachsen et al, 2012;Volkov et al, 2013;Raj et al, 2016). However, how far these vortices are advected and how often they reach deep into the LB is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…The exchange of AW with the LB (AW-LB exchange) has also been studied extensively. Earlier literature has suggested that much of the warm AW in the LB stems from anticyclonic eddies in the form of long-lived coherent vortices that shed off from the Slope Current and then bring with them heat and vorticity westward into the basin (Köhl, 2007;Isachsen et al, 2012;Volkov et al, 2013;Raj et al, 2016). However, how far these vortices are advected and how often they reach deep into the LB is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Thus for a sinusoid, the amplitude and phase assigned using the analytic signal method agree with the obvious choices, i.e., a x (t) = a o and φ x (t) = ω o t + φ o . This crucial property is known as harmonic correspondence (Vakman, 1996). The canonical phase can be differentiated to give the instantaneous frequency (Gabor, 1946;Picinbono, 1997),…”
Section: The Analytic Signalmentioning
confidence: 99%
“…A compelling argument in favor of the analytic signal method is due to Vakman (1996); see also Huang and Yang (2011). Consider assigning a time-varying amplitude and phase by pairing the real-valued signal x(t) with some other imaginary part than its Hilbert transform.…”
Section: Analytic Signal Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eddies having more negative values of relative vorticity would experience a type of instability known as inertial or centrifugal instability. Consequently such eddies are not observed in nature, with the most intense documented anticyclones, such as the Lofoten Basin Eddy(Søiland and Rossby, 2013;Bosse et al, 2019;Trodhal et al, 2020), having vorticities of around ζ = −f . This stability boundary corresponds to a nondimensional frequency of ω(t) = −1/2.Inertial oscillations typically occur at a Fourier frequency of ω = −f or ω(t) = −1, with the negative sign indicating that inertial oscillations turn clockwise in the Northern Hemisphere and counterclockwise in the Southern Hemisphere.…”
mentioning
confidence: 99%